2017
DOI: 10.1021/acs.biochem.7b00970
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Conformational Changes Associated with the Maturation of Thrombin Anion Binding Exosite I

Abstract: Thrombin participates in procoagulation, anticoagulation, and platelet activation. This enzyme contains anion binding exosites, ABE I and ABE II, which attract regulatory biomolecules. As prothrombin is activated to thrombin, pro-ABE I is converted into mature ABE I. Unexpectedly, certain ligands can bind to pro-ABE I specifically. Moreover, knowledge is lacking on changes in conformation and affinity that occur at the individual residue level as pro-ABE I is converted to ABE I. Such changes are transient and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(56 citation statements)
references
References 68 publications
(187 reference statements)
3
52
1
Order By: Relevance
“…28 NMR buffer composed of 25 mM H 3 PO 4 , 150 mM NaCl, and 0.2 mM EDTA (pH 6.5) was used to dilute the peptide for future NMR studies. 28…”
Section: Synthetic Peptidesmentioning
confidence: 99%
See 3 more Smart Citations
“…28 NMR buffer composed of 25 mM H 3 PO 4 , 150 mM NaCl, and 0.2 mM EDTA (pH 6.5) was used to dilute the peptide for future NMR studies. 28…”
Section: Synthetic Peptidesmentioning
confidence: 99%
“…were employed. 28 To minimize serine protease autolysis, a 4:1 complex of PPACK to thrombin was incubated at 37 °C for 30 min. Employing a Vivaspin 2 ultrafiltration unit (5000 Da) from Sartorius (Göttingen, Germany), ProT and PPACK-thrombin samples were exchanged into NMR buffer (pH6.5).…”
Section: D Proton Line Broadening and 2d Transferred Noesy Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…These NMR titrations demonstrate that PAR3 residues document structural rearrangements occurring during exosite maturation that are missed by reported X-ray crystal structures. 50,154 Later, the project was extended to better understand the diversity of PAR ligand binding interactions towards zymogen ProT vs mature thrombin. 1D proton line broadening confirmed that PAR1P (49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62) and weaker binding version PAR1G (49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62) already exhibited line broadening with ProT and such broadening increased when bound to thrombin.…”
Section: Discussionmentioning
confidence: 99%